2008
DOI: 10.1002/glia.20682
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine receptor CXCR2 is differentially regulated on glial cells in vivo but is not required for successful remyelination after cuprizone‐induced demyelination

Abstract: Unravelling the factors that can positively influence remyelination is one of the major challenges in multiple sclerosis research. Expression of the chemokine receptor CXCR2 on oligodendrocytes both in vitro and in MS lesions has suggested a possible role for CXCR2 in the recruitment of oligodendrocyte precursor cells (OPC). To investigate the function of CXCR2 during remyelination in vivo, we studied this receptor in cuprizone-induced demyelination and subsequent remyelination. We found that CXCR2 is constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…The latter chemokine is released by reactive astrocytes and is known to halt OPC differentiation in vivo (Tsai et al 2002). However, this concept has not been supported by cuprizone-induced demyelination in CXCR2-deficient mice, as no impaired OPC recruitment has been observed (Lindner et al 2008). The controversial role of CXCL1/CXCR2 remains to be investigated further.…”
Section: Cxcl1-cxcl8: Cxcr2 Ligandsmentioning
confidence: 97%
“…The latter chemokine is released by reactive astrocytes and is known to halt OPC differentiation in vivo (Tsai et al 2002). However, this concept has not been supported by cuprizone-induced demyelination in CXCR2-deficient mice, as no impaired OPC recruitment has been observed (Lindner et al 2008). The controversial role of CXCL1/CXCR2 remains to be investigated further.…”
Section: Cxcl1-cxcl8: Cxcr2 Ligandsmentioning
confidence: 97%
“…Histology for Luxol-fast blue periodic acid-Schiff base (LFB-PAS) and immunohistochemistry were performed as previously described [20]. Paraffin embedded sections were de-waxed, rehydrated, and microwaved for 5 min in 10 mM citrate buffer (pH 6.0).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…In addition, it was shown that CXCR2 activation might directly contribute to motor neuron degeneration [61]. Since the expression of CXCR2 has also been detected in neurons, astrocytes and microglia [62][63][64], more work is required to understand the role of CXCR2 in the CNS both in normal and disease conditions.…”
Section: Nonhematopoietic Cells and Cells Of The Central Nervous Systemmentioning
confidence: 99%